Analisis Kesesuaian Lahan Untuk Kawasan Industri di Kabupaten Kendal Berdasarkan Arahan Rencana Tata Ruang Wilayah Kabupaten Kendal - Putri Ivanya; Najma Alifia; Amanda Azra Salsabhila; Lia Marliana; Noval Tri Nugroho; Difa Azzahra; Cahyadi Setiawan (Jurnal Pendidikan Geografi Undiksha, 2026)
Massive industrial estate development in Kendal Regency has caused agricultural land conversion and potential spatial planning inconsistencies. This study aims to evaluate land suitability levels for industrial estates and their alignment with the 2011–2031 Regional Spatial Plan (RTRW) of Kendal Regency. The method employs a quantitative descriptive approach using Geographic Information Systems (GIS) through overlay and buffering techniques on six physical land parameters. The results indicate that the Kendal region is generally dominated by the Moderately Suitable category (57.55%). However, specifically within the designated industrial zones in the RTRW, the land is dominated by the Marginally Suitable class (58.27%), with the Highly Suitable class reaching only 5.51%. This indicates that the planned industrial locations possess dominant physical limiting factors, requiring appropriate technical engineering and strict environmental management to ensure optimal and sustainable land utilization.